2017
DOI: 10.1038/s41431-017-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

Care and cost consequences of pediatric whole genome sequencing compared to chromosome microarray

Abstract: The clinical use of whole-genome sequencing (WGS) is expected to alter pediatric medical management. The study aimed to describe the type and cost of healthcare activities following pediatric WGS compared to chromosome microarray (CMA). Healthcare activities prompted by WGS and CMA were ascertained for 101 children with developmental delay over 1 year. Activities following receipt of non-diagnostic CMA were compared to WGS diagnostic and non-diagnostic results. Activities were costed in 2016 Canadian dollars (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…It has been previously shown that WGS, while an expensive test, may actually decrease overall cost (particularly downstream cost) of diagnostic evaluations of medically complex children. 12 Although also appearing to reduce rather than increase costs in our cohort, the impact of precision medicine could not be quantified in seven of 13 infants without a group of matched historical controls and/or long-term follow up (see Supplementary Results ). However, the short-term impact on healthcare utilization was quantified in the remaining six infants (Table 3 , Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It has been previously shown that WGS, while an expensive test, may actually decrease overall cost (particularly downstream cost) of diagnostic evaluations of medically complex children. 12 Although also appearing to reduce rather than increase costs in our cohort, the impact of precision medicine could not be quantified in seven of 13 infants without a group of matched historical controls and/or long-term follow up (see Supplementary Results ). However, the short-term impact on healthcare utilization was quantified in the remaining six infants (Table 3 , Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This is well illustrated by a recent study that compared children with suspected genetic disease who had initial chromosomal microarray analysis and subsequent diagnostic genome sequencing. 14 The volumes and costs of medical interventions prompted by negative chromosomal microarray results and diagnostic GWS results were quantitatively similar but qualitatively different. Negative chromosomal microarray analysis sometimes led to additional laboratory investigations in pursuit of a diagnosis, while obtaining a diagnosis by genome sequencing often led to more visits to medical specialists or allied health professionals, reflecting changes in clinical management.…”
Section: Introductionmentioning
confidence: 98%
“…The change in medical management is thus commonly used as an indicator of clinical utility, where a measure of outcome can be captured at three instances: (i) the return of results, (ii) documented changes to clinical management, and (iii) measures of long-term clinical outcome 24 . While many studies focused on describing the changes in acute management brought about by a positive genetic diagnosis, very few have assessed the long-term impact by longitudinal follow-up of >1 year 3 , 19 , 25 29 . Furthermore, the impact on reproductive decisions for both the affected individuals and their families is often limited.…”
Section: Introductionmentioning
confidence: 99%